Energy and morality - Wolfe, Lynne; Gall, Michael; Boylan, Richard F.; Wolfe, Swain; Bitterroot Films (Oley, PA : Bullfrog Films, 1979)
Presents contrasts of social effects of high-level and low-level energy usage on human behavior and value systems. Uses narrative, animation and interviews with energy experts Amory Lovings and E.F. Schumacher to explore the relationship between the energy available to society and the values that control the behavior of society
Copy in DVD Format
Narrated by Katherine White ; with Sarah Crump ... [et al.]
VHS Format
Keywords: Energy conservation -- Social aspects; Energy consumption -- Social aspects; Energy development -- Social aspects; Energy policy -- Social aspects